Princess Mia - 413064 Cabot, Meg (New York, NY : HarperTeen, 2008)
While Mia tries to get over breaking up with her boyfriend, she discovers a diary kept by a former princess of Genovia from the 1600s, the contents of which could change the fate of her country forever.